Сумісне одержання ненасичених карбонових кислот та їх естерів гетерогенно-каталітичною конденсацією карбонільних сполук - Небесна, Юлія Віталіївна (Національний університет "Львівська політехніка", 2016)
Дисертація присвячена розробленню основ технології сумісного одержання ненасичених карбонових кислот та їх естерів методом альдольної конденсації карбонільних сполук в газовій фазі на твердих каталізаторах. Розроблено високоефективну каталітичну систему складу В2O3–Р2O5–ZrO2/SiO2 для процесу газофазної конденсації метилпропіонату з формальдегідом, застосування якої дозволяє одержувати одразу два цінні мономери –метилметакрилат та метакрилову кислоту. Розроблена каталітична система також є ефективною у процесі сумісного одержання метилакрилату та акрилової кислоти. Встановлено залежності між якісним і кількісним складом розроблених каталізаторів та їх фізико-хімічними і каталітичними властивостями. Встановлено кінетичні закономірності процесу сумісного одержання метилметакрилату та метакрилової кислоти в присутності кращої каталітичної системи. На основі розробленої кінетичної моделі розраховано та експериментально підтверджено оптимальні технологічні параметри здійснення процесу. Розроблено основи технології сумісного одержання метилметакрилату та метакрилової кислоти. Диссертация посвящена разработке основ технологии совместного получения ненасыщенных карбоновых кислот и их эфиров методом альдольной конденсации карбонильных соединений в газовой фазе на твердых катализаторах. Разработана высокоэффективная каталитическая система состава B2O3 – P2O5 –ZrO2/SiO2 для процесса газофазной конденсации метилпропионата с формальдегидом, использование которой позволяет получать сразу два ценных мономера – метилметакрилат и метакриловую кислоту. Разработанная каталитическая система также является эффективной в процессе совместного получения метилакрилата и акриловой кислоты. Определены зависимости между качественным и количественным составом разработанных катализаторов и их физико-химическими и каталитическими свойствами. Определены кинетические закономерности процесса совместного получения метилметакрилата и метакриловой кислоты в присутствии лучшей каталитической системы. На основе разработанной кинетической модели рассчитаны и экспериментально подтверждены оптимальные технологические параметры процесса. Разработаны основы технологии совместного получения метилметакрилата и метакриловой кислоты. The thesis is devoted to the development of technology basics of simultaneous obtaining of unsaturated carboxylic acids and their esters by aldol condensation of saturated esters and formaldehyde in the gas phase over solid catalysts. Catalytic systems based on mixtures of oxides of boron and phosphorus promoted with different oxides were prepared. Silica gel with large specific surface area was used as a support for catalyst preparing. Total amount of active components in the catalyst was 20 %. Aldol condensation reaction of methyl propionate and formaldehyde was studied in the presence of created catalysts. The main products were methyl methacrylate and methacrylic acid; propionic acid, methanol and diethyl ketone were formed too. Equimolar ratio of methyl propionate to formaldehyde was found to be the best for the process. It was observed that adding of methanol causes decreasing of total yield of methyl methacrylate and methacrylic acid. Residence time of 12 s was found to be the best for aldol condensation of methyl propionate and formaldehyde. Forming of large amount of propionic acid over the catalyst promoted by tungsten oxide was observed. The catalysts promoted by basic oxides show high selectivity at low temperatures, but conversion of methyl propionate is too low. Using zirconium oxide as promoter provides the highest selectivity among other studied oxides of transient metals. The highest total yield and selectivity of methyl methacrylate and methacrylic acid was observed in the presence of a catalyst with molar ratio of ZrO2/P2O5 0.3. Over this catalyst at the optimum temperature of 623 K the one-pass total yield of methacrylate monomers is 63.2 % while with recycling of methyl propionate and propionic acid it can be increased to 87.5 %. The best catalytic system was studied in the aldol condensation process of methyl acetate and formaldehyde yielding methyl acrylate and acrylic acid. The optimum temperature for methyl acrylate and acrylic acid producing is the temperature of 653 K. The maximum total yield of methyl acrylate and acrylic acid is 72.2 % while their total selectivity is 77.4 % and conversion of methyl acetate is 93.2 %. The correlation between physical-chemical properties of developed catalysts and their catalytic activity was determined. It was found that catalyst's activity correlates with their total surface acidity, and methacrylates selectivity has negative correlation with a strength of the acid active sites. It was established that condensation process of methyl propionate with formaldehyde most favorably occurs in the pores with radius 3.6–6 nm on the weak acid active sites with Еа NH3 less than 30 kJ/mol. The best catalyst was used to study the kinetic regularities of the aldol condensation of methyl propionate with formaldehyde. The mechanism of this reaction was proposed. The kinetic model of the reaction was developed and based on it optimum conditions were calculated and confirmed experimentally to be temperature of 623 K and residence time of 13 s. Under this conditions one-pass total yield of methacrylate monomers is 64.7 % while with recycling of methyl propionate and propionic acid it can be increased to 87.6 %. The technology basics of simultaneous obtaining of methyl methacrylate and methacrylic acid have been elaborated.
Совместное получение ненасыщенных карбоновых кислот и их эфиров гетерогенно-каталитической конденсацией карбонильных соединений
Simultaneous obtaining of unsaturated carboxylic acids and their esters by heterogeneous catalytic condensation of carbonyl compounds
Keywords: метилметакрилат; метакрилова кислота; метилакрилат; акрилова кислота; формальдегід; альдольна конденсація; гетерогенний каталіз; метилметакрилат; метакриловая кислота; метилакрилат; акриловая кислота; формальдегид; альдольная конденсация; гетерогенный катализ; methyl methacrylate; methacrylic acid; methyl acrylate; acrylic acid; formaldehyde; aldol condensation; heterogeneous catalysis